A New Approach to the Economic Problem of Dumping based on Game Theory with Grey Parameters - Davood Darvishi Selokolayi; Samira Heydari Gorji (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Dumping is one of the negative results of free trade. It occurs when a foreign exporter sells a commodity at a lower price than the selling price of the same or similar commodity in its domestic market in another country's market. Many approaches are used to investigate the problem of dumping, one of which is game theory, which is used in this article. Methodology: Game theory is one of the advanced scientific phenomena that has provided a solid framework for strategic behaviours. A lot of data is needed to solve business problems and issues, and given that real-world data usually involves uncertainty, using definite methods in a real, inaccurate environment will not be suitable for optimal decision-making. Therefore, this article intends to study the issues of dumping and anti-dumping in countries' trade relations with the help of game theory in the environment of grey uncertainty. Findings: According to the results, since healthy competition in a product's market leads to the desirability and reduction of the price of that product, the formation of healthy competition requires appropriate policies and policies for businesses to survive in a competitive market or be strengthened in those markets. Originality/Value: Game theory is one of the applied fields that has grown in decision-making and economics and has attracted the attention of many researchers. Utilizing this theory can help the current knowledge about the further application of this theory in the country's economic conditions.